Phonological Level Language Errors in the Compositions of Class XI DKV Vocational High School Students - Amalia, Lois Aura; Markhamah, M (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to analyze language errors in students' compositions, the factors causing language errors, and solutions to reduce the occurrence of language errors Methodology: This study uses a qualitative descriptive method. Data collection techniques used in this study are observation, reading techniques, note-taking techniques, and interviews. Data analysis techniques in this study use interactive data analysis techniques Results: The results of the study found language errors in the field of phonology which include errors in the use of capital letters, periods, commas, italics, and spelling errors. Factors that cause language errors include relaxed and informal habits, lack of opportunities to write according to the rules, lack of understanding of language rules or good and correct language rules, and laziness to pay attention to the use of good and correct language rules. Applications/Originality/Value: Solutions that can be done to reduce language errors include creating a habit of writing according to good and correct language rules or rules, when giving assignments, teachers still pay attention to the writing done by students, and students can read and understand PUEBI and read more books to improve writing skills. This research is expected to be a reference for improvement that can be implemented in students' writing according to linguistic rules.